Decline and Extermination of an Arctic Wolf Population in East Greenland, 1899–1939 - Marquard-Petersen, Ulf (ARCTIC, 2012)
The decline and extermination of an arctic wolf population in East Greenland between 1899 and 1939 were investigated through analysis of 40 years of archival data, which contained records of 252 sightings of wolves or their tracks. Prior to the start of exploitation by Europeans, this small, isolated wolf population probably consisted of about 38 wolves during an average year. Of 112 wolves sighted in early winter, 31.3% were lone wolves, 23.2% were in pairs, and the rest were in larger groups. Mean pack size was 3.3 wolves, and packs of more than four wolves were rare. The population was concentrated in the central part of its range, making it vulnerable to exploitation by Danish and Norwegian commercial hunters, who exterminated the population. Poison was the primary agent of destruction. There was no evidence that other proposed causes of the decline were influential. This study provided the first evidence of an arctic wolf population that was eradicated and highlights the vulnerability of small, isolated wolf populations to excessive harvest. Wolves in the High Arctic may be particularly vulnerable because of their exceptionally low densities, smaller pack sizes, lower pup production, infrequent reproduction, and insular or disjunct distributions. Le déclin et l’extermination d’une population de loups arctiques dans l’est du Groenland entre 1899 et 1939 a fait l’objet d’une enquête prenant la forme de l’analyse de données archivées s’étendant sur 40 années. Ces données comprenaient l’enregistrement de 252 observations de loups ou de pistes de loups. Avant que cette région ne soit exploitée par les Européens, cette petite population de loups isolée comptait probablement environ 38 loups au cours d’une année moyenne. Au début de l’hiver, 112 loups avaient été observés, dont 31,3 % étaient des loups seuls, 23,2 % se trouvaient en paires et le reste étaient en groupes plus volumineux. La taille moyenne d’une meute était de 3,3 loups, tandis que les meutes comptant plus de quatre loups se faisaient rares. Cette ...